Overview of New EPA Regulations Affecting Use of Metam Sodium and Metam Potassium - Andrew MacRae; Joseph Noling (EDIS, 2010)
HS1167, a 10-page fact sheet by Andrew MacRae and Joseph Noling, provides a general overview of the new mitigation measures growers and certified applicators will be required to implement, based on the new reregistration eligibility decisions (REDs) for metam sodium and metam potassium. Published by the UF Department of Horticultural Sciences, April 2010.